2018
DOI: 10.1186/s12887-018-1032-z
|View full text |Cite
|
Sign up to set email alerts
|

Neutropenia after intravenous immunoglobulin therapy is associated with coronary artery lesions in children with Kawasaki disease: a case control study

Abstract: BackgroundTo evaluate differences in laboratory parameters, clinical presentation, and incidence of coronary artery lesions (CAL) between children with neutropenic and non-neutropenic Kawasaki disease (KD).MethodsAll consecutive KD patients that presented to the Second Affiliated Hospital and Yuying Children’s Hospital of Wenzhou Medical University in Wenzhou, China between January 2005 and December 2015 were included in this study. Patients were divided into two groups (KD with neutropenia (NKD) and KD withou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
3
1
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 15 publications
1
3
1
1
Order By: Relevance
“…It was also pointed out that early neutropenia within the 10th day of disease onset played an important role in the prevention of CALs (16). In contrast, we found no significant differences in CALs in patients with and without neutropenia with baseline equilibrium after 1:4 propensity score matching, which was in line with Wang's study, although they set the time of CALs at a 3-month follow-up (17). The divergence was caused by different study designs, as we did not specifically focus on the time of neutropenia onset.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…It was also pointed out that early neutropenia within the 10th day of disease onset played an important role in the prevention of CALs (16). In contrast, we found no significant differences in CALs in patients with and without neutropenia with baseline equilibrium after 1:4 propensity score matching, which was in line with Wang's study, although they set the time of CALs at a 3-month follow-up (17). The divergence was caused by different study designs, as we did not specifically focus on the time of neutropenia onset.…”
Section: Discussionsupporting
confidence: 91%
“…Otherwise, some other confounders might also play roles. Our results were not totally in line with a previous study, in which the authors showed patients with ANC larger than 6 had greater CALs rates (17). We attributed the divergence to the following reasons.…”
Section: Discussioncontrasting
confidence: 84%
See 1 more Smart Citation
“…Severe adverse events are considered to be rare, but may include anaphylaxis, aseptic meningitis, acute renal failure, thromboembolic events, and transfusion-related acute lung injury [15][16][17][18][19]. Neutropenia following IVIG therapy has been observed in case reports and series of neurological, hematological, and pediatric patients [20][21][22][23][24][25][26][27][28][29]. To the best of our knowledge, data on IVIG-induced hematological side effects in dermatological cohorts are restricted to a recent case series by Cicha et al [30].…”
Section: Introductionmentioning
confidence: 99%
“…Severe adverse events are considered to be rare, but may include anaphylaxis, aseptic meningitis, acute renal failure, thromboembolic events, and transfusion-related acute lung injury [15][16][17][18][19]. Neutropenia following neurological, hematological, and pediatric patients [20][21][22][23][24][25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%